2022
DOI: 10.1111/syen.12544
|View full text |Cite
|
Sign up to set email alerts
|

Integrative taxonomy solves taxonomic impasses: a case study from Epyrinae (Hymenoptera, Bethylidae)

Abstract: We apply integrative taxonomy to solve a historical taxonomic impasse in a flat wasp group (Hymenoptera, Bethylidae). The phylogeny of Epyrinae is inferred with parsimony analyses under equal and implied weights, maximum likelihood and Bayesian inference using the nuclear markers 18S and 28S, the mitochondrial genes 16S, cytochrome oxidase subunit I and cytochrome B and 232 morphological characters. This is the first phylogenetic study to examine all 42 epyrine genera, including junior synonyms and extinct tax… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 65 publications
1
10
0
Order By: Relevance
“…Indeed, these morphology-based hypotheses do not fully align with molecular-based hypotheses (Carr et al 2010;de Brito et al 2022;Colombo et al 2022) and many deep relationships remain undeciphered. While a sister-group relationship of Mesitiinae and Scleroderminae has been repeatedly found (Carr et al 2010: using 'Cephalonomiini' in place of Scleroderminae;de Brito et al 2022;Colombo et al 2022), morphological analyses including extinct lineages retrieve the Mesitiinae in different positions [sister-group to all extant Bethylidae but Bethylinae in Colombo et al (2020); sister-group to all extant subfamilies here].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Indeed, these morphology-based hypotheses do not fully align with molecular-based hypotheses (Carr et al 2010;de Brito et al 2022;Colombo et al 2022) and many deep relationships remain undeciphered. While a sister-group relationship of Mesitiinae and Scleroderminae has been repeatedly found (Carr et al 2010: using 'Cephalonomiini' in place of Scleroderminae;de Brito et al 2022;Colombo et al 2022), morphological analyses including extinct lineages retrieve the Mesitiinae in different positions [sister-group to all extant Bethylidae but Bethylinae in Colombo et al (2020); sister-group to all extant subfamilies here].…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, these morphology-based hypotheses do not fully align with molecular-based hypotheses (Carr et al 2010;de Brito et al 2022;Colombo et al 2022) and many deep relationships remain undeciphered. While a sister-group relationship of Mesitiinae and Scleroderminae has been repeatedly found (Carr et al 2010: using 'Cephalonomiini' in place of Scleroderminae;de Brito et al 2022;Colombo et al 2022), morphological analyses including extinct lineages retrieve the Mesitiinae in different positions [sister-group to all extant Bethylidae but Bethylinae in Colombo et al (2020); sister-group to all extant subfamilies here]. Similarly, the Pristocerinae has been found to be sister of the Epyrinae (Carr et al 2010: using 'Epyrini' instead of Epyrinae) or [Epyrinae + Protopristocerinae] (Colombo et al, 2020; this study), but other molecular analyses found it as sister to all extant subfamilies but the Bethylinae (de Brito et al 2022;Colombo et al 2022).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Among the five extant subfamilies, the Pristocerinae are the one with the most evident sexual dimorphism, in which the females are apterous, with extremely reduced eyes and without ocelli, while the males are macropterous, with developed eyes and ocelli (Azevedo et al 2016, 2018). On the contrary, in the Epyrinae, the Mesitiinae and the most of Bethylinae, the sexual dimorphism is minimal (see Azevedo et al 2018; Colombo et al 2022), with few cases of evident morphological characteristics, as in epyrine genus Calyoza Hope, in which males have a pectinate antenna and the flagellomere I is extremely reduced, like as a ring‐shaped, whereas females have a filiform antenna and the flagellomere I is the same size as the latter ones (for more details, see Colombo et al 2022), and Bethylus Latreille, which females of several species are polymorphic with apterous, brachypterous and macropterous forms (Richards 1939).…”
Section: Discussionmentioning
confidence: 99%
“…Following the key to the subfamilies of Bethylidae of Azevedo et al (2018), this specimen keys in the Epyrinae for the fully-developed wings, without Rs+M, the metanotum short, the metapectal-propodeal complex without posterior spines, the metasomal segment 2 regularly long, the mesopleuron with transepisternal line, the fore wing with anterior margin straight and C present. Following the key to the genera of Epyrinae of Colombo et al (2022b), it keys between Epyris Kieffer, 1914 and Bakeriella Kieffer, 1910 for the mesoscuto-mesoscutellar foveae not connected by sulcus, the posterior ocelli broadly separated, the dorsal pronotal area without elevation anteriorly and the anterior margin not incurved, the anterior area of sternite 2 without flap and the antennae not pectinate, the mesoscuto-mesoscutellar foveae separated by less than half their own length, the metapectalpropodeal disc with distinct metapostnotal-propodeal carina. However, some features merely indicate Bakeriella for the present fossil: the body with metallic reflections, as is visible in some Bakeriella but not in Epyris (Azevedo et al, 2018); the mesoscuto-mesoscutellar foveae subelliptical rather than rectangular, a pattern of Bakeriella (e.g., Azevedo, 2014: figs.…”
Section: Systematic Remarks the Specimen Possesses Numerous Features ...mentioning
confidence: 99%